2010
DOI: 10.1111/j.1471-4159.2010.06809.x
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 receptor activation induces CXCL2 production in microglia through NFAT and PKC/MAPK pathways

Abstract: J. Neurochem. (2010) 114, 810–819. Abstract Microglia plays an important role in many neurodegenerative conditions. ATP leaked or released by damaged cells triggers microglial activation through P2 receptors, and stimulates the release of oxygen radicals, proinflammatory cytokines and chemokines from activated microglia. However, little is known about mechanisms underlying ATP‐induced chemokine release from microglia. In this study, we found that a high concentration of ATP induces the mRNA expression and rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(73 citation statements)
references
References 77 publications
3
65
0
Order By: Relevance
“…A previous study demonstrated that P2X7-mediated sensing of ATP induced the activation of several signal transduction pathways leading to the activation of microglia (Shiratori et al, 2010). In the present study, the involvement of ERK MAP kinases in the activation of basophils and mast cells was demonstrated.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…A previous study demonstrated that P2X7-mediated sensing of ATP induced the activation of several signal transduction pathways leading to the activation of microglia (Shiratori et al, 2010). In the present study, the involvement of ERK MAP kinases in the activation of basophils and mast cells was demonstrated.…”
Section: Discussionmentioning
confidence: 54%
“…Extracellular ATP activates ERK1 and/or ERK2 (ERK1/2) to induce cellular responses (Shiratori et al, 2010;Swanson et al, 1998). Therefore, we analyzed ATP-induced phosphorylation of ERK1/2 in basophils and mast cells ( Figure 6A).…”
Section: Regulation Of Autocrine Atp-dependent Activation By E-npp3mentioning
confidence: 99%
“…While it seems clear that CN is intimately involved in neuroinflammation, much work is still needed to fully assess the specific interactions between CN-dependent and -independent transcription factors, and how these interactions regulate specific inflammatory phenotypes. While this review has focused primarily on the role of CN in astrocytes, other work showing similar roles of CN in microglia [56-58,74] underscores the necessity to characterize the signaling properties of CN in other glial subtypes. Furthermore, the identification of other cellular targets of CN, including glutamate transporters, gap junctions, and BACE, suggests that CN’s impact on glial function may extend well beyond immune/inflammatory signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Both P2X7Rs and P2Y 6 Rs appeared to be involved [146]. In microglia, ATP induced messenger RNA (mRNA) expression and release of CCL2, CCL3, and CXCL2 mainly through activation of P2X7Rs [151][152][153]. Chemokine production was mediated via both calcineurindependent nuclear factor of activated T cells (NFAT) and PKC/MAPK signaling pathways.…”
Section: Inflammatory Chemokines(c-c Motif) Ligandsmentioning
confidence: 97%